General Public’s knowledge, awareness, and perception of Cardiometabolic diseases: data from a Singapore study population - Anand, Vickram Vijay; Goh, Rachel Sze Jen; Nah, Benjamin; Koh, Sky Wei Chee; Lim, Jieyu; Neo, Nicholas W. S.; Chew, Jocelyn; Lee, Yuan Ying; Chin, Yip Han; Chong, Bryan; Kong, Gwyneth; Tan, Bryan; et al. (Frontiers in medicine, 2023)
Health literacy and illness perception play crucial roles in tackling the cardiometabolic disease epidemic. We aim to compare the attitudes, knowledge, self-perceived risks and actions taken, between individuals with and without metabolic risk factors (MFs). From 5 June to 5 October 2022, participants of the general public were invited to complete a self-administered questionnaire. MF status was defined as the presence of hypertension, hyperlipidemia, diabetes mellitus and/or current/previous smoking. Participants were assessed based on four categories (knowledge-based, attitude-based, perceived risk, and action-based) of questions pertaining to four cardiometabolic diseases - diabetes mellitus, hypertension, hyperlipidemia, and non-alcoholic fatty liver disease. A total of 345 participants were enrolled, of whom 34.5% had at least one MF. Compared to those without MFs, participants with MFs had lower knowledge scores, but higher perceived risk scores across all cardiometabolic diseases. The largest knowledge gap pertained to hypertension-related questions. After adjustment, linear regression demonstrated that the presence of MFs (β:2.752, 95%CI: 0.772-4.733, = 0.007) and higher knowledge scores (β:0.418, 95%CI: 0.236-0.600, < 0.001) were associated with higher perceived risk. Despite increased perceived risk in those with MFs, this translated to only few increased self-reported preventive actions, when compared to those without MFs, namely the reduction in red meat/processed food consumption ( = 0.045) and increase in fruits/vegetables consumption ( = 0.009). This study identified a vulnerable subpopulation living with MFs, with high perceived risks, and discordant levels of knowledge and preventive actions taken. Nationwide efforts should be channeled into addressing the knowledge-to-action gap.